Pengaruh Lingkungan Kerja dan Insentif Terhadap Semangat Kerja Karyawan Pada Beach And Beat Cafe Pandan Kabupaten Tapanuli Tengah - Andini Rara Putri; Mhd. Shafwan Koto; Riwayani Riwayani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Work Environment and Incentives on Employee Work Spirit at Beach And Beats Cafe Pandan, Central Tapanuli Regency. This research uses a quantitative method with descriptive and associative approaches. The population consists of 33 employees, all of whom are used as the sample (saturated sampling). Data collection techniques include questionnaires, interviews, and documentation. Data analysis methods include validity test, reliability test, classical assumption test, correlation analysis, coefficient of determination, multiple linear regression, and hypothesis testing (t-test and F-test). The results show that all research instruments are valid and reliable, and the data are normally distributed. Partially, Work Environment has a positive and significant effect on Work Spirit with t-value 3.442 > t-table 2.042 and significance value 0.002 < 0.05. Incentives also have a positive and significant effect on Work Spirit with t-value 6.023 > t-table 2.042 and significance value 0.001 < 0.05. Simultaneously, Work Environment and Incentives have a positive and significant effect on Work Spirit with F-value 48.204 > F-table 3.32 and significance value 0.001 < 0.05. The coefficient of determination (R²) is 0.763, indicating that 76.3% of Work Spirit variation is explained by Work Environment and Incentives, while the remaining is influenced by other variables not examined in this study.